1990
DOI: 10.1097/00001888-199002000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Comparing information-gathering strategies of medical students and physicians in diagnosing simulated medical cases

Abstract: Using a broad range of written patient management problems (PMPs), this study examined (1) how each of three medical information-gathering processes (history-taking, physical examination, and diagnostic studies) influenced 175 second-year medical students' formulations of the differential (i.e., plausible) and the principal (i.e., most probable) diagnoses for each of 14 PMPs, and (2) the extent to which these results paralleled the emphases that experienced clinicians placed on these same information-gathering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

1992
1992
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 0 publications
0
9
0
1
Order By: Relevance
“…The question remains, however, whether medical students are able to make the same use of information. Although studies of physician decision making are used to place emphasis on med-ical history as a diagnostic tool [4,5,7], there are few studies that directly examine the influences of the histxy, physical examination, and diagnostic studies on the diagnostic decision making of medical students.…”
mentioning
confidence: 99%
“…The question remains, however, whether medical students are able to make the same use of information. Although studies of physician decision making are used to place emphasis on med-ical history as a diagnostic tool [4,5,7], there are few studies that directly examine the influences of the histxy, physical examination, and diagnostic studies on the diagnostic decision making of medical students.…”
mentioning
confidence: 99%
“…OSCE scores among clinical clerks were higher on history-taking/physical examination skills (mean score ± s.d., 61 ± 4%) and interviewing skills (69 ± 11%), and lower on problem solving (50 ± 6%) skills [33]. In a non-OS CE examination using patient management problems, second-year students scored 70 ± 9% on history, 66 ± 10% on physical examination, and 40 ± 15% on diagnosis [34]. However, in an OSCE for a second-year neurology skills course, this pattern did not hold: interpretative skill scores (76 ± 16%) were higher than technical performance scores (67 ± 17%), but no significance testing was reported [15].…”
Section: Discussionmentioning
confidence: 99%
“…With the PMP method, multiple options (20-30 options in one study and 15-40 options in another) for narrowing down the disease or for differential diagnosis are presented with respect to the case history, physical examination, and laboratory tests. 3,4 Thus, the actual diagnostic reasoning process, in which options must be generated by the doctor or study, may not be reflected. Research has shown a weak positive correlation among the processes of data inquiry, data interpretation and integration, and diagnosis elaboration, raising the issue of interdependence between these skills.…”
Section: Introductionmentioning
confidence: 99%